Quicken 2013 for dummies - Nelson, Stephen L. (John Wiley & Sons, 2013)
In this newest edition of his perennial favorite guide, financial expert and bestselling author Stephen Nelson shows how taking control of your finances can be quick and effortless with Quicken, the number one personal finance software on the market. Providing you with a thorough introduction to all the latest features and enhancements to the newest version, Nelson shows you how to use the program to track your income and expenses, maximize savings, pay your bills, manage your investments, and balance your checkbook